Fructooligosaccharides production and the health benefits of prebiotics - Gonçalves, Clarisse Salomé Nobre (2022)
Dietary prebiotics have been associated with the prevention and treatment of many 21st-century diseases. Prebiotics health benefits have been linked to microbiomehost complex interactions, modulating microbiota homeostasis, gutbrain axis, microbiotaimmune system crosstalk, and the intestine barrier function. There is therefore huge interest from industry in successfully developing bioprocesses for their production. Fructooligosaccharides (FOS) production at a large scale is clearly of the utmost importance as their health benefits have been reported in numerous studies. This chapter provides an overview of the emergent biotechnological processes being developed to produce FOSs with a high conversion yield and content. Taking into consideration that new compounds are now appearing as promising prebiotic candidates due to the recently established definition of prebiotics, current studies of prebiotic effects on specific diseases, including well-established and emergent prebiotics, are also reviewed, including information on the dosage administered, its mechanisms of action, and evidence found.